2012
DOI: 10.1016/j.ajo.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia Keratitis: Clinical Course and Effect of Corticosteroids

Abstract: Purpose To compare the clinical course of Nocardia spp keratitis with keratitis due to other bacterial organisms, and to assess the effect of corticosteroids as adjunctive therapy using data collected from the Steroids for Corneal Ulcers Trial (SCUT). Design Sub-group analysis of a randomized controlled trial Methods Setting Multicenter randomized controlled trial Study Population 500 patients with bacterial keratitis, randomized 1:1 to topical corticosteroid or placebo who had received at least 48 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 20 publications
(23 reference statements)
1
30
0
2
Order By: Relevance
“…Because previous analyses of SCUT have shown that Nocardia ulcers did poorly with topical steroids, we performed a similar analysis stratified by causative organism. 10 Although these analyses were consistent with a harmful effect of topical corticosteroids for Nocardia ulcers and a beneficial effect for non-Nocardia ulcers, we found no statistically significant difference between the treatment arms: in Nocardia ulcers, corticosteroids were associated with a 2. …”
Section: Resultssupporting
confidence: 40%
“…Because previous analyses of SCUT have shown that Nocardia ulcers did poorly with topical steroids, we performed a similar analysis stratified by causative organism. 10 Although these analyses were consistent with a harmful effect of topical corticosteroids for Nocardia ulcers and a beneficial effect for non-Nocardia ulcers, we found no statistically significant difference between the treatment arms: in Nocardia ulcers, corticosteroids were associated with a 2. …”
Section: Resultssupporting
confidence: 40%
“…Once the correct diagnosis was confirmed and amikacin started, steroids were again applied, this time without incident. However, recent research indicates that corticosteroids may actually be detrimental in Nocardia species keratitis and may lead to larger scars at 3 and 12 months (Srinivasan, et al, 2014), (Lalitha, et al, 2012), (Garg & Vazirani, 2013). In light of this recent research and our own experience with this case, we believe that corticosteroids should not be applied in the treatment of Nocardia species keratitis.…”
Section: Discussionmentioning
confidence: 80%
“…Even with the use of antimicrobial agents, corticosteroids still may be associated with less favourable outcomes in treating keratitis related to some microorganisms such as Nocardia 46 and atypical Mycobacteria 51 52. Moreover, there is no convincing evidence of benefit from the addition of corticosteroids to the treatment of fungal keratitis; it is more likely to be harmful as corticosteroids interfere with the efficacy of many antifungal agents in vivo, and enhance fungal replication 53–56.…”
Section: Clinical Trialsmentioning
confidence: 99%